INFLUENTIAL OF ECONOMIC GROWTH, MANPOWER ABSORPTION ON PUBLIC WELFARE - Daengs, Achmad; Mahjudin, Mahjudin (Optimum: Jurnal Ekonomi dan Pembangunan, 2017)
Economic growth is an eï¬ ort to accelerate the pace of development due to the acceleration of economic growth will be able to push the performance of the sectors there are other more eï¬ cient and productive. High economic growth would create a larger distribution of income and improve public welfare. Investment growth plays an important role in economic growth, because investment is a signiï¬ cant component of expenditure that will aï¬ ect demand and also aï¬ ect employment opportunities. This study aims to determine the eï¬ ect of private investment, public investment on economic growth and employment as well as the livelihoods of the urban districts in East Java province. Variables used in this study is composed of exogenous variables private investment and government investment; endogenous variables, namely the welfare of society; intervening variable of economic growth and man power absorption. The data used are time coherent data covering the period 2003-2008 in 38 districts / municipalities in East Java province.